Potensi dan Tantangan TikTok sebagai Media Edukasi Kesehatan Mental Generasi Muda - Adha, Aziza Zahrotul; Kurnia, Galuh Mega; Qomaruddin, Mochammad Bagus; Widati, Sri (Universitas Airlangga, 2025)
Background: TikTok is a social media application that has become popular among the younger generation due to its short, creative, and straightforward content. These aspects can render TikTok a potential application for mental health education. However, the downsides of lacking credibility checks and the potential for spreading misinformation exist and can be harmful to users. Objectives: This scoping review aims to explore the potential and challenges of TikTok as a medium for mental health education. Methods: This study employed a scoping review approach. Three databases were employed in the data review: Science Direct, ProQuest, and PubMed. ‘Mental Health’ and ‘TikTok’ were the primary keywords. After rereading each paper with consideration for the relevance and lucidity of the findings, it was determined that 16 articles were suitable for this evaluation. Results: TikTok may be used as a platform of mental health education, awareness-raising, and support due to its wide reach and interactive nature. Its effectiveness relies on the content type and quality, psychological characteristics of users, and credibility checks. Minimizing the danger of misinformation and emotional disturbance of users is a concern. There needs to be more media literacy, content regulation, and active participation of mental health professionals in content creation to harness the TikTok platform to its full potential as a mental health education tool. Conclusions: TikTok can to be a powerful tool for mental health education and literacy, but its effectiveness is contingent on content quality, user characteristics, and credibility filtering. To realize maximum gains and reduce the risk of spreading misinformation and injurious content, strict moderation, regulation, and user education are required.